Velocity specificity of resistance training - Behm, D. G.; Sale, D. G. (Sports Medicine, 1993)
Velocity specificity of resistance training has demonstrated that the greatest strength gains occur at or near the training velocity. There is also evidence that the intent to make a high speed contraction may be the most crucial factor in velocity specificity. The mechanisms underlying the velocity-specific training effect may reside in both neural and muscular components. Muscular adaptations such as hypertrophy may inhibit high velocity strength adaptations due to changes in muscle architecture. However, some studies have reported velocity-specific contractile property adaptations suggesting changes in muscle kinetics. There is evidence to suggest velocity-specific electromyographic (EMG) adaptations with explosive jump training. Other researchers have hypothesised neural adaptations because of a lack of electrically evoked changes in relation to significant voluntary improvements. These neural adaptations may include the selective activation of motor units and/or muscles, especially with high velocity alternating contractions. Although the incidence of motor unit synchronisation increases with training, its contribution to velocity-specific strength gains is unclear. However, increased synchronisation may occur more frequently with the premovement silent period before ballistic contractions. The preprogrammed neural circuitry of ballistic contractions suggests that high velocity training adaptations may involve significant neural adaptations. The unique firing frequency associated with ballistic contractions would suggest possible adaptations in the frequency of motor unit discharge. Although co-contraction of antagonists increases with training and high velocity movement, its contribution is probably related more to joint protection than the velocity-specific training effect.